تحليل مفهوم الجاهلية في فكر سيد قطب - Abdalla El-Banna, I.; Mohd Daud, N.A. (Universiti Sains Islam Malaysia, 2024)
The study investigates the notion of “jahiliyya” according to Sayyid Qutb. It covers the discussion on the demarcation line between Islamic and jahiliyya societies and Qutb’s justification of considering societies in general as under the shadow of Jahiliyyah. The study also analyses views from supporters of Qutb and also the opponents of his view in regards to the notion. Using qualitative methodological framework, the study characterizes, compares and appraises Qutb’s views on ‘jahiliyyah’ based on his writings and others. It can be concluded that ‘jahiliyyah’ addressed by Qutb exemplifies the ideas of man’s judgement over man in the one hand, and the non-acknowledgement of God’s supremacy by giving a due recognition of man’s lordship in the other. The study also summed up that jahiliyyah in Qutb’s discourse predominantly carries the meaning of backwardness, certain values, attitudes and deviation. Those prescribed meanings are altogether in line with the literal sense of the word.